A Comparative Analysis of the Chloroplast Genomes of Four Salvia Medicinal Plants. (October 2019) - Liang, Conglian; Wang, Lei; Lei, Juan; Duan, Baozhong; Ma, Weisi; Xiao, Shuiming; Qi, Haijun; Wang, Zhen; Liu, Yaoqi; Shen, Xiaofeng; Guo, Shuai; Hu, Haoyu; et al.
Abstract: Herbgenomics is an emerging field of traditional Chinese medicine (TCM) research and development. By combining TCM research with genomics, herbgenomics can help to establish the scientific validity of TCM and bring it into wider usage within the field of medicine. Salvia Linn. ( S . Linn.) is a large genus of Labiatae that includes important medicinal plants. In this herbgenomics study, the complete chloroplast (cp) genomes of two Salvia spp.—namely, S. przewalskii and S. bulleyana, which are used as a surrogate for S. miltiorrhiza —were sequenced and compared with those of two other reported Salvia spp.—namely, S . miltiorrhiza and S. japonica . The genome organization, gene number, type, and repeat sequences were compared. The annotation results showed that both Salvia plants contain 114 unique genes, including 80 protein-coding, 30 transfer RNA (tRNA), and four ribosomal RNA (rRNA) genes. Repeat sequence analysis revealed 21 forward and 22 palindromic sequences in both Salvia cp genomes, and 17 and 21 tandem repeats in S . przewalskii and S . bulleyana, respectively. A synteny comparison of the Salvia spp. cp genomes showed a high degree of sequence similarity in the coding regions and a relatively high divergence of the intergenic spacers. Pairwise alignment and single-nucleotide polymorphism (SNP) analyses found some candidate fragments to identify Salvia spp., such as the intergenic region of the trnV–ndhC, trnQ–rps16, atpI–atpH, psbA–ycf3, ycf1, rpoC2, ndhF, matK, rpoB, rpoA, and accD genes. All of the results—including the repeat sequences and SNP sites, the inverted repeat (IR) region border, and the phylogenetic analysis—showed that S . przewalskii and S . bulleyana are extremely similar from a genetic standpoint. The cp genome sequences of the two Salvia spp. reported here will pave the way for breeding, species identification, phylogenetic evolution, and cp genetic engineering studies of Salvia medicinal plants.